2021
DOI: 10.1186/s12872-021-02416-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of carotid plaque in a mixed HIV-serostatus cohort in Uganda

Abstract: Background The extent to which the risk of atherosclerotic cardiovascular disease (ACVD) is increased among people living with HIV (PLWH) in sub-Saharan Africa remains unknown. Setting Cross-sectional analysis nested within the Ugandan Noncommunicable Diseases and Aging Cohort, including PLWH in rural Uganda > 40 years taking antiretroviral therapy (ART) for at least 3 years, and a population-based control group of HIV-uninfected age- and sex-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…We found that being HIV positive on ART was associated with 3.78 times higher odds of CA. This is similar to the ndings of other researchers [50,51]. There is evidence that HIV infection promotes in ammatory processes in humans and accelerates atherogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…We found that being HIV positive on ART was associated with 3.78 times higher odds of CA. This is similar to the ndings of other researchers [50,51]. There is evidence that HIV infection promotes in ammatory processes in humans and accelerates atherogenesis.…”
Section: Discussionsupporting
confidence: 91%